UNRAVELING THE ROLE OF EPIGENETIC MODIFICATIONS IN GENE REGULATION A MOLECULAR GENETICS PERSPECTIVE - AL-Abedi, Yasameen Waleed; Halboti, Alaa Abdalhadi; Saleh, Ali Abdulhussein (PT. Antis International Publisher, 2024)
Epigenetic modifications is very crucial in managing on/off switch of the genes, and the kind of cell that is being built. The specific goals of this study are to identify the role of histone modifications, DNA methylation, and their interaction with each other on gene expression according to the ChIP-Seq, RNA-Seq, and bisulfite sequencing results. Therefore, in order to offer wide and profound analysis we went to specify the strains for regulatory components, to describe the molecular events, and to contemplate concerning potential clinical utility. Typically, for ChIP-Seq analysis, the number of histone modification peaks varies between 5,000-10,000 per sample, which is the comparison to the input control With regards to the genomic location of these peaks 60-70% of these are in promoter regions, while 20-30% of these are in enhancers. Described variation in RNA-Seq brought about 1000–3000 DE genes per condition; in the compared conditions, the difference generally ranged from 2 to 10 folds. Specifically, 500-1500 of them had different methylation between the control and the patient group with different methylation variations; 20%-60%. Thus, the integration of these datasets demonstrated that there exists significant relationships between histone modification and gene expression level, with the former ment for active modification leading to up-regulation of genes and the latter for repressive modification leading to down- regulation of genes. Besides, the report determined that hypomethylation of promoters of genes led to overexpression whereas hypermethylation of promoters of genes l led to underexpression. The functional enrichment of the genes with the epigenetic changes revealed mostly the cell cycle and signal transduction based on the Gene Ontology.